Association between serum potassium levels and short-term mortality in patients with atrial fibrillation or flutter co-treated with diuretics and rate- or rhythm-controlling drugs. Issue 3 (2nd July 2019) - Hagengaard, Louise; Søgaard, Peter; Espersen, Marie; Sessa, Maurizio; Lund, Peter Enemark; Krogager, Maria Lukács; Torp-Pedersen, Christian; Kragholm, Kristian Hay; Polcwiartek, Christoffer
Abstract: Aims: We investigated the association between potassium levels and 90-day all-cause mortality in atrial fibrillation or flutter (AF) patients co-treated with diuretics and rate- or rhythm-controlling drugs. Methods and results: During 2000–12, first-time AF patients treated with beta-blockers, amiodarone, sotalol, verapamil, or digoxin combined with any diuretic within 90 days post-AF discharge were included. Following co-treatment, a potassium measurement within 90 days after initiating diuretic treatment was required. Mortality risk associated with potassium <3.5, 3.5–3.7, 3.8–4.0, 4.5–4.7, 4.8–5.0, and >5.0 mmol/L (reference: 4.1–4.4 mmol/L) was assessed using multivariable Cox regression. In total, 14 425 AF patients were included (median age: 78 years; women: 52%). Patients most often received beta-blocker monotherapy (29%), beta-blockers and digoxin combined (25%), digoxin monotherapy (24%), amiodarone monotherapy (3%), and verapamil monotherapy (3%). Increased 90-day mortality risk was associated with <3.5 mmol/L [hazard ratio (HR) 2.05, 95% confidence interval (CI) 1.68–2.50], 3.5–3.7 mmol/L (HR 1.28, 95% CI 1.05–1.57), 4.5–4.7 mmol/L (HR 1.20, 95% CI 1.02–1.41), 4.8–5.0 mmol/L (HR 1.37, 95% CI 1.14–1.66), and >5.0 mmol/L: (HR 1.84, 95% CI 1.53–2.21). Compared with beta-blocker monotherapy, rate- or rhythm-controlling drugs did not modify the association between potassium groups and mortality risk. Conclusion: In addition to hypo- and hyperkalaemia, low and high normal range potassium levels were associated with increased 90-day mortality risk in AF patients co-treated with diuretics and rate- or rhythm-controlling drugs. These associations were independent of rate- or rhythm-controlling drugs.